2019
DOI: 10.3390/ijms20081899
|View full text |Cite
|
Sign up to set email alerts
|

L-Lysine as the Molecule Influencing Selective Brain Activity in Pain-Induced Behavior of Rats

Abstract: Lysine-rich proteins are some of the most important proteins of neurons and it has become necessary to investigate the possible role of L-lysine as a brain functioning regulator. The purpose of our study is to identify the characteristics and the mechanisms of L-lysine effects on the different types of pain-induced behavior in the stimulation of tail and foot-shock models in 210 adult male Wistar rats. L-lysine was administered in intraperitoneal or intracerebroventricular injections in doses of 0.15–50.0 µg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…l -Lysine, by itself and in conjunction with l -arginine, has also been shown to protect against ischemic insults resulting from suppression of glutamate-induced neuronal activity [ 151 ]. Recently, l -lysine was shown to affect pain-induced behavior in rats [ 152 ].…”
Section: Amino Acidsmentioning
confidence: 99%
“…l -Lysine, by itself and in conjunction with l -arginine, has also been shown to protect against ischemic insults resulting from suppression of glutamate-induced neuronal activity [ 151 ]. Recently, l -lysine was shown to affect pain-induced behavior in rats [ 152 ].…”
Section: Amino Acidsmentioning
confidence: 99%
“…As discussed before for L-3-methylhistidine, this discriminatory capability persisted throughout the TH process (see Fig 3 ). Lysine is an essential amino acid expressed particularly in neuronal proteins, and it is directly involved in modulating gene expression [ 33 ]. Experimental studies on murine models also suggest that this amino acid has a neuroprotective [ 34 ] and anti-inflammatory role.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies suggest an increase in pain threshold when using lysine. 89 By participating in collagen synthesis and antibody production, it promotes accelerated tissue repair and infection control. Studies have shown a positive action of this amino acid in reducing the healing time of lesions caused by herpesviruses (HHV-1 and HHV-6\7), the number of lesions (HHV-6/7) and the severity of lesions (HHV-1 and HHV-6 \7).…”
Section: Role In Physiology and Ability Of The Virus To Establish Inf...mentioning
confidence: 99%